LEGAL ANALYSIS OF CHILD CUSTODY RIGHTS IN CASES OF DIVORCE - Dikki Saputra Saragih; Rolando Marpaung; Malthus Hutagalung; Seni Fifi Meriani Zalukhu (PT. Radja Intercontinental Publishing, 2023)
Child protection law No. 23 of 2020 article 14, which states that